SISTER EVA MICHALAK, AT THE AGE OF NINETY FOUR, A RESEARCHER AND SELF TAUGHT THAT WITH HER WISDOM GATHERED ONE OF THE LARGER COLLECTIONS OF MEDICINAL AND FRUITBEARING PLANTS OF THE SANTA CATARINA STATE (Revista de Ciências Agroveterinárias, 2006)
Entrevista com Irmã Eva Michalak.
Keywords: interview; Eva Michalak.